2001
DOI: 10.1111/j.1530-0277.2001.tb02254.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Milk Intake After Exposure to Alcohol in Mothers' Milk

Abstract: These findings demonstrate that short-term exposure to small amounts of alcohol in mothers' milk produces distinctive changes in the infants' patterns of feeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 21 publications
2
30
1
3
Order By: Relevance
“…25 In an interesting study of the effect of alcohol on milk ingestion by infants, the rate of milk consumption by infants during the 4 hours immediately after exposure to alcohol (0.3 g/kg) in 12 mothers was significantly less. 26 Reduction of letdown is apparently dosedependent and requires alcohol consumption of 1.5 to 1.9 g/kg. 27 Other studies have suggested psychomotor delay in infants of moderate drinkers (>2 drinks daily).…”
Section: Recreational Drugsmentioning
confidence: 99%
“…25 In an interesting study of the effect of alcohol on milk ingestion by infants, the rate of milk consumption by infants during the 4 hours immediately after exposure to alcohol (0.3 g/kg) in 12 mothers was significantly less. 26 Reduction of letdown is apparently dosedependent and requires alcohol consumption of 1.5 to 1.9 g/kg. 27 Other studies have suggested psychomotor delay in infants of moderate drinkers (>2 drinks daily).…”
Section: Recreational Drugsmentioning
confidence: 99%
“…There is an extensive animal and human literature that addresses the role that fetal and postnatal learning about ethanol’s chemosensory attributes plays in later perception, preference and intake of ethanol (Abate et al, 2000, 2001; Arias and Chotro, 2005; Chotro and Arias, 2003; Faas et al, 2000; Mennella, 1999, 2001; Mennella and Beauchamp, 1998; Molina et al, 1995, 1999; Spear and Molina, 2001, 2005). With specific respect to in utero exposure, when ethanol is present as a stimulus in the amniotic fluid of the developing fetus its presence can later lead to a memory of ethanol’s sensory-related cues as well as an association between both its sensory attributes and its unconditioned properties (Abate et al, 2000, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This clinical box highlights some of the issues related to alcohol use from a developmental perspective. 164,165,[199][200][201][202][203][204][205][206][207][208][209] Prenatal • Fetal alcohol syndrome and fetal alcohol effects are part of the fetal alcohol spectrum of disorders. • Prenatal exposure to alcohol puts the developing fetus at risk for developmental disabilities.…”
Section: Alcohol and Developmentmentioning
confidence: 99%